Investigation and Implementation of Beacon Technology for Man Tracking in Oil and Gas Industry - Firdaus, Hamizah Fasihah Hairanil; Subramaniam, Siva Kumar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The oil and gas industry deals with various challenges, and one of it is to comply with frequently changing environmental regulations in monitoring and management system. In this project, the focus will be in the necessity for oil and gas industry to monitor the movement of their employees especially for whom that were conducting tasks in remote areas to wisely optimise the runway resources while simultaneously reaching the needs of delivery schedules. To oversee the workers position, a comprehensive floor mapping system that indicates the real-time status of individuals is required on 24/7 basis. Therefore, the use of beacon system with IOT platform will be applied in this project. The concept is such as the employees are required to carry a customised beacon badge, for this badge will communicate valuable information to the Bluetooth gateway that coordinates the collected information to a cloud-based system for floor mapping process. In other words, an investigation and implementation of a beacon system through a Bluetooth gateway to a cloud-based system in accordance with IEEE 802.15 standard will work out.